Competitive IPOs - Jenkinson, T; Jones, H (Blackwell Publishing Ltd., 2009)
Competition between investment banks for lead underwriter mandates in IPOs is fierce, but having committed to a particular bank, the power of the issuer is greatly reduced. Although information revelation theories justify giving the underwriters influence over pricing and allocation, this creates the potential for conflicts of interest. In this clinical paper we analyse an interesting innovation that has been used in recent European IPOs whereby issuers separate the preparation and distribution roles of investment banks, and keep competitive pressure on the banks throughout the issue process. These ‘competitive IPOs’ allow the issuer greater control and facilitate more contingent fee structures that help to mitigate against ‘bait and switch.’ But unlike more radical departures from traditional bookbuilding – such as auctions – the competitive IPO is an incremental market-based response to potential conflicts of interest that retains many of the advantages of investment banks’ active involvement in issues.